2019
DOI: 10.1097/corr.0000000000001091
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities are Present in the Timing of Radiographic Assessment and Surgical Treatment of Hip Fractures

Abstract: Survey Background This report is part of a series titled "Discrimination in America." The series is based on a survey conducted for National Public Radio, the Robert Wood Johnson Foundation, and Harvard T.H. Chan School of Public Health. The survey was conducted January 26-April 9, 2017, among a nationally representative, probability-based telephone (cell and landline) sample of 3,453 adults age 18 or older. The survey included nationally representative samples of African Americans, Latinos, Asian Americans, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 34 publications
5
82
1
Order By: Relevance
“…While we did not analyze the impact of patient characteristics, such as race or ethnicity, on timeliness of care, other studies have found that nonwhite patients may be subject to assessment and treatment delays in the ED. 18,19 If similar trends hold true in our sample, it is possible that our study underestimates the magnitude of difference in high-acuity care timeliness between FREDs and HEDs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…While we did not analyze the impact of patient characteristics, such as race or ethnicity, on timeliness of care, other studies have found that nonwhite patients may be subject to assessment and treatment delays in the ED. 18,19 If similar trends hold true in our sample, it is possible that our study underestimates the magnitude of difference in high-acuity care timeliness between FREDs and HEDs.…”
Section: Discussionsupporting
confidence: 52%
“…Of note, as previously demonstrated, 11 we found that the baseline characteristics of patient visits to FREDs and HEDs were different, with FREDs tending to serve fewer minority patients. While we did not analyze the impact of patient characteristics, such as race or ethnicity, on timeliness of care, other studies have found that nonwhite patients may be subject to assessment and treatment delays in the ED 18,19 . If similar trends hold true in our sample, it is possible that our study underestimates the magnitude of difference in high‐acuity care timeliness between FREDs and HEDs.…”
Section: Discussionmentioning
confidence: 83%
“…International evidence illustrates how racial and ethnic groups experience disparities in triage scores, 14 radiographic assessment, 15 coronary angiography, 16 surgical waiting times 17 and analgesia recommendations 18 . Studies have shown that Indigenous Australians have a higher admission rate, 19 greater severity of illness 19 and higher burden of cardiometabolic comorbidities 20 .…”
Section: Introductionmentioning
confidence: 99%
“…5) In another study of 5 intraregional hospitals, the authors found that black patients had a significantly longer delay to radiography and surgery from initial presentation. 6) To better understand the effects of race on hip fracture care across a wider set of hospitals, our objective was to determine whether race is associated with longer time to surgery from hospital presentation and increased perioperative complications by using the National Surgical Quality Improvement Program (NSQIP).…”
mentioning
confidence: 99%
“… 5) In another study of 5 intraregional hospitals, the authors found that black patients had a significantly longer delay to radiography and surgery from initial presentation. 6) …”
mentioning
confidence: 99%